Avaliação de uma intervenção para prevenção da violência no namoro - Priolo Filho, Sidnei Rinaldo (Universidade Federal de São Carlos, 2017)
This thesis is developed with four articles presenting the trajectory and development of an intervention to prevent dating violence among Brazilian adolescents. At first, a pilot study was conducted with 34 adolescents, divided into control and experimental group, evaluating their behaviors and the themes, duration and number of sessions of the intervention. The results of this pilot indicated a decrease in the violence practiced by the adolescents, measured by the Conflict Tactics Scale - Revised (CTS-2). After the pilot, the instruments had their instructions adapted and a questionnaire about attitudes on violence was added. The definitive study was performed consisting of an intervention with 94 adolescents randomly divided into control and experimental groups with pre and post-test collections. Participants responded to the standardized Brazilian Socioeconomic Status (SES), the Alcohol Use Identification Test (AUDIT), the Conflicts Tactics Scale – Revised (CTS-2), and a questionnaire on beliefs about violence. The experimental group placed questions about the themes in a sealed ballot boxes in the classroom to increase the participation of adolescents. These questions were analyzed and categorized qualitatively. Sessions on sexuality occurred with separation between males and females, with the facilitator of these sessions of the same gender of the group. The experimental group had follow-up data collections 3, 6 and 12 months after the intervention. Participants asked 117 questions during the intervention, and most part of those questions were related to sexuality, followed by social problem-solving and relationships. Males asked a greater number of questions related to sexuality, compared to the girls. Post-test results show a decrease in frequency of aggressive behaviors practiced and suffered for the experimental group, as well as the number of participants who were aggressive. The experimental group also showed a significant decrease in sexual violence practiced and suffered in the post-test, as well as in the number of adolescents who consumed alcohol. However, after one year the experimental group did not show differences in relation to the post-test, but all the frequencies were numerically inferior when compared to the pretest. Sexual violence remained significantly lower after 12 months of intervention for the experimental group. However, there was a significant increase in alcohol consumption after 12 months, especially among women. The results of the intervention point in promising directions for future research with Brazilian adolescents by presenting important decreases in violent behaviors practiced and suffered, especially for sexual violence. Therefore, future research should consider themes and presentation of this work, however, looking for ways to involve the school and families in a more effective maintenance of the aggressive behaviors after the intervention.
Keywords: Adolescentes; Prevenção; Violência contra o parceiro; Adolescents; Prevention; Violence against the partner; CIENCIAS HUMANAS::PSICOLOGIA